(untitled) (Research, Society and Development, 2022)
Discussing issues related to sexuality has become a challenge for teachers, so it is important to train teachers prepared to guide and discuss in the classroom the multiple aspects related to human sexuality. This work consists of reporting the characteristics (hours, menu, objectives, and strategies) of the discipline "Education for sexuality - faces and interfaces in teacher training" offered for the degree course in Biological Sciences at the Federal University of Triângulo Mineiro (UFTM) as well as the description of its development over four offers. The discipline aims to support students in teaching content/strategies aimed at sexuality education, enabling a more effective application of content in basic education. The theoretical workload is 45h/a, in addition to 15h/a of practical activities, totaling 60h/a and 30 vacancies are available annually. The offer was made only four times since the beginning of the course in 2009. Considering the total number of students in the course, we can consider that only 33% showed interest in the course, 12% of the students completed the course and 21% only enrolled, but never attended. Students’ frequent classes remain until their completion. The bibliography consulted, the reality of the offer of the discipline, and the reports of the students who attended the curricular component point to the need for disciplines that focus on teacher training in line with education for sexuality, since the licentiate can work and deal with the theme will be prepared to act in the classroom in different circumstances.